Drooling Reduction Intervention randomised trial (DRI): comparing the efficacy and acceptability of hyoscine patches and glycopyrronium liquid on drooling in children with neurodisability. Issue 4 (30th November 2017) - Parr, Jeremy R; Todhunter, Emma; Pennington, Lindsay; Stocken, Deborah; Cadwgan, Jill; O'Hare, Anne E; Tuffrey, Catherine; Williams, Jane; Cole, Mike; Colver, Allan F
Abstract : Objective: Investigate whether hyoscine patch or glycopyrronium liquid is more effective and acceptable to treat drooling in children with neurodisability. Design: Multicentre, single-blind, randomised controlled trial. Setting: Recruitment through neurodisability teams; treatment by parents. Participants: Ninety children with neurodisability who had never received medication for drooling (55 boys, 35 girls; median age 4 years). Exclusion criteria: medication contraindicated; in a trial that could affect drooling or management. Intervention: Children were randomised to receive a hyoscine skin patch or glycopyrronium liquid. Dose was increased over 4 weeks to achieve optimum symptom control with minimal side-effects; steady dose then continued to 12 weeks. Primary and secondary outcomes: Primary outcome: Drooling Impact Scale (DIS) score at week-4. Secondary outcomes: change in DIS scores over 12 weeks, Drooling Severity and Frequency Scale and Treatment Satisfaction Questionnaire for Medication; adverse events; children's perception about treatment. Results: Both medications yielded clinically and statistically significant reductions in mean DIS at week-4 (25.0 (SD 22.2) for hyoscine and 26.6 (SD 16) for glycopyrronium). There was no significant difference in change in DIS scores between treatment groups. By week-12, 26/47 (55%) children starting treatment were receiving hyoscine compared with 31/38 (82%) on glycopyrronium. There was a 42% increased chance of being on treatment at week-12 for children randomised to glycopyrronium relative to hyoscine (1.42, 95% CI 1.04 to 1.95). Conclusions: Hyoscine and glycopyrronium are clinically effective in treating drooling in children with neurodisability. Hyoscine produced more problematic side effects leading to a greater chance of treatment cessation. Trial registration numbers: ISRCTN75287237 ; EUDRACT: 2013-000863-94; Medicines and Healthcare Products Regulatory Agency: 17136/0264/001-0003